PENGARUH PEMAHAMAN PAJAK, SANKSI PAJAK, DAN SENSUS PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PRIBADI YANG MEMILIKI USAHA - Sochi Rusmawati; Dewi Kusuma Wardani (Jurnal Akuntansi, 2015)
This study was conducted to verify the effect of understanding the taxpayer, tax penalties, and the national tax census of the personal tax compliance have a business. This study uses the dependent variable is the personal tax compliance have a business and independent variables that is an understanding of the taxpayer, tax penalties, and the national tax census. The sampling technique used was simple random sampling technique to 50 individual taxpayers who have a business located in Sinduadi, Mlati, Sleman. Data collection procedures by submitting the form of a direct question questionnaire and interviews with personal taxpayers who have a business. The analysis technique used is multiple regression with SPSS 16.0 tools. Based on the result indicate that the variable understanding of the taxpayer, tax penalties, and the national tax census proved significant simultaneous effect on tax compliance has a business person. Predictive ability of these three variables on tax compliance shows the independent variables can explain the variation in the dependent variable of 72.3% and the rest is explained by other variables. Keywords: understanding taxes, tax penalties, tax census and tax compliance